2022
DOI: 10.1186/s12909-022-03580-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Infectious Diseases training in the perception of antibiotic resistance and rational use of antibiotics among Spanish medical students – a cross-sectional study

Abstract: Background Antibiotic resistance is one of the main public health problems worldwide. One key tool to optimize antibiotic prescription is medical training. The aim of this study is to compare the impact of training in infectious diseases on students’ knowledge of the antibiotic resistance problem and the rational use of antibiotics. Methods We performed a cross-sectional study in the medical school of the University of Navarra. We conducted an anon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…A cross-sectional study conducted among 994 medical students in Spain established the effect of the inclusion of infectious disease training in the final year curriculum on the knowledge of students regarding antimicrobial stewardship which increased from 9.3% in the first year to 52.2% in the sixth year of the degree program ( P < .05). 21 This study also established that when an intervention like a training session on AMS was conducted among medical students, the mean AMS knowledge score increased from 59.92 ± 8.10 to 68.56 ± 5.92 ( P < .05).…”
Section: Discussionsupporting
confidence: 55%
“…A cross-sectional study conducted among 994 medical students in Spain established the effect of the inclusion of infectious disease training in the final year curriculum on the knowledge of students regarding antimicrobial stewardship which increased from 9.3% in the first year to 52.2% in the sixth year of the degree program ( P < .05). 21 This study also established that when an intervention like a training session on AMS was conducted among medical students, the mean AMS knowledge score increased from 59.92 ± 8.10 to 68.56 ± 5.92 ( P < .05).…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, a study conducted among United Arab Emirates medical students revealed that study year was a strong determinant of KAP regarding antibiotic use and knowledge, as final year students scored more highly than first-year students [ 23 ]. Furthermore, a study of Spanish medical students found that knowledge of antibiotic stewardship increased significantly after they received infectious diseases (ID) training in their fifth and sixth-years, in comparison to students in their first three years of education without ID training [ 24 ]. Consistent with our study, a survey of 291 Polish medical students, in their first to third years, found they had a high level of knowledge (91.1%) regarding the efficacy of antibiotics against viral infections [ 25 ].…”
Section: Discussionmentioning
confidence: 99%